EXPLORING SPATIAL TRANSFORMATION ON JAVA TRADITIONAL HOUSES BASED ON THE HIERARCHY OF NEEDS - Alrizqi, Muhammad Rafli; Kurniawan, Harry (Built Environment Studies, 2024)
Housing is one of the basic human needs that is dynamic and more than just a place to shelter, so changes based on needs are inevitable. In the house, spatial organization often changes so that it transforms, especially in traditional Joglo houses that face pragmatic changes or still follow traditional values. A qualitative research approach was conducted using the observation method, combined with in-depth interviews, and integrated with Maslow's hierarchy of needs theory. Maslow divides the needs into five levels. Therefore, it is essential to understand changes in spatial and household needs. In this study, we found five cases of Joglo houses, spaces used for commercial activities economically tend to come from esteem and self-actualization needs; another five Joglo houses with spaces used as a place for social and cultural activities; based on belonging, esteem needs, and self-actualization; and another two Joglo houses that have spaces transformed and or converted into personal spaces based on fundamental and safety needs. Our findings show that spatial had altered based on user needs in a bottom-up and reciprocal manner. This can be demonstrated by the absence of massive facades and spatial layout changes, which still maintain spaces that are considered essential, such as senthong, gandhok, and pendhapa. Spatial transformation is also influenced by the capabilities and background of Joglo house owners, who mostly have businesses and or come from respected families to maintain the legacy of Joglo houses and make the house a residence and a symbol of prosperity and well-being. In addition, with spatial transformation, Joglo houses can still meet the needs of users/residents to the level of self-actualization. This study offers a new perspective on combining a hierarchy of needs and spatial transformation, specifically in joglo traditional houses.